Motivasi Kerja Terhadap Kinerja Tenaga Kesehatan Berbasis Implementasi Kompetensi dan Komunikasi Organisasi - Adya Hermawati; Yuli Purbaningsih; La Iwe; I Wayan Ruspendi Junaedi; Teguh Setiawan Wibowo (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This research uses explanatory research. The variables of this research are competence (X1), organizational communication (X2), work motivation (Z), and performance of health workers (Y). The research subjects or units of analysis were all health personnel of the Griya Husada Hospital as well as the population of this study, with a sample of 57 health workers. The type of data used in this research is quantitative data which is the data from the questionnaire. Data analysis used inferential statistical analysis and analysis. The results showed that organizational competence and communication have an influence on work motivation. Organizational communication and work motivation have an influence on performance. Competence does not affect the performance of health workers. Work motivation is able to mediate the relationship of organizational communication to performance. And, work motivation is not able to mediate the relationship between the performance of health workers at Griya Husada Hospital.